Developing practice and informing policy: A case study of inter-agency collaboration to support students who experience emotionally based school refusal - Steel-Brewster, Martyn (2015)
There is a clear link between attendance and attainment showing that pupils with low-levels of attendance are less likely to achieve academically. Some students struggle to attend school due to emotionally based reasons. As a consequence, their future employability and life choices may be reduced and their risk of psychiatric illness in adulthood is increased. Better intervention and appropriate training are needed to prevent this from happening. This practitioner inquiry advocates an inter-agency approach to support young people who experience anxiety or emotionally based school refusal (EBSR). Inter-agency collaboration causes contradictions and tensions to emerge. These contradictions were explored to promote new professional learning. Barriers to interagency working were researched and a working group identified the following potential barriers to future working: a lack of clarity regarding roles and responsibilities, a lack of clarity regarding goals, communication between agencies and management of the project. This study also explored the additional challenges that leaders of multi-profession teams encounter. Even though there are significant barriers and challenges associated with inter-agency collaboration and its leadership, when viewed as a vehicle to generate new ways of thinking and working, it provides leaders with a real opportunity to improve the life chances for young people with EBSR.